Synthesis and Antibacterial Testing of Imina Derivative Compounds from Piperonal and Anilin - Dimas Syamsudin; Ismiyarto Ismiyarto; Ngadiwiyana Ngadiwiyana (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2018)
Synthesis of Imine derivates used as antibacterial activity has been done. Synthesis was conducted by condensation reaction between piperonal and aniline. The product synthesis was characterized by melting point, LC-MS, FTIR and 1H-NMR, then application of the product as antibacterial towards bacteria Staphylococcus aureus and Escherichia coli. The product of synthesis was pale-brown solid, and had melting point at 56-61 0C. Identification by LC-MS showed the compound molecular weight was 225.30 gram/mol, identification by FTIR showed a compound contained imine C=N at 1620.21 cm-1, C-H aromatic at 1581.63 cm-1, Csp3-H at 2962.37 cm-1 from CH2, and C-O at 1265.30 cm-1, Identification by 1H-NMR showed a compound had a singlet peak at δ=6 ppm that proton was from the CH2, multiplet peak at δ=6.9-7.7 ppm proton from two aromatics and singlet peak at δ=8.4 ppm from proton imine. The minimum inhibitory concentration of the product towards Staphylococcus aureus and Escherichia coli was 1 mg/mL with diameter inhibition zone 2 mm and 3 mm. From these data it could be concluded that the compound 3,4- methlenedioxybenzilyimine was formed and it had ability as an antibacterial agent.